A conceptual framework for reputational capital development: An exploratory study of first-time FTSE 100 NED appointees. - Gaughan, Mary (Cranfield University, 2013)
This thesis seeks to explore and understand the appointment process of first-time FTSE 100 NEDs. It has been widely acknowledged for over three decades that the appointment process of NEDs is an opaque process involving a homogeneous group of people in an ‘old boys’ network. Corporate governance reforms recommend a formal and transparent appointment process which taps into a wider pool of talent. Companies comply with these recommendations yet there has been scant change in the composition of corporate boards. The pilot study consisted of nine interviews with the main stakeholders in the appointment process of a NED, namely Chairman, Executive Search Firms and NEDs. Analysis of the interview transcripts revealed that reputational capital was the basis on which a first-time NED appointment was made after the Chairman had carried out an extensive vetting process to establish the fit of the individual. The main study, based on 15 first-time FTSE 100 NED interviews, sought to understand reputational capital, its constituent parts and how individuals developed it. Further, it sought to explore how an individual’s fit for a NED was established. The analysis revealed that the reputational capital of an appointed NED was a blend of sufficient levels of human, social and cultural capital which had been communicated to the Chairman and other members of the corporate elite. A first-time NED, in gaining a foothold on a corporate board was also entitled to membership of the corporate elite. As reputational capital drives success of directors in the corporate elite, new individuals needed to fit with the norms and values appropriate for membership and carry no reputational risk for existing members particularly the Chairman. This research offers three main contributions to the literature. Firstly, at a theoretical level it extends the concept of board capital to include cultural capital in addition to human and social capital. Secondly, it proposes a conceptual framework which demonstrates how an individual builds reputational capital over the course of a career to secure fit for a first- time NED, as a position in the corporate elite. The framework clarifies our understanding of reputational capital as a combination of human, social and cultural capital in a unique blend of board capital. This board capital is communicated through reputation building activities to members of the corporate elite. Thirdly, at an empirical level it provides an understanding of the FTSE 100 NED appointment process.
Keywords: Reputational capital; board capital; cultural capital; corporate elite; corporate governance